Best Answer

If you do not know what y is equal to then you can not evaluate this. If it is equal to zero then y is equal to 6/5.

Q: What is the answer -5y plus 6 equal to?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6-1y+(5y-6y) = 6-y+(-1y) = 6

5y = 3y + 12 5y - 3y = (3y - 3y) + 12 2y = 12 y = 6

4x+5y = 30 5y = -4x+30 y = -4/5x+6 in slope intercept form So the y intercept is 6.

9y+3 = 5y+13 9y-5y = 13-3 4y = 10 y =2.5

(6x)(5y)

Related questions

It equals x+5y simplified

6y + 5y = -66 11y = -66 (-66/11 = y) y = -6

It is an expression that can be simplified to 5y+2x-6

6 - y + 5y - 6y = 6 - 2y

5y + 6

5y+8 = 7y-6 5y-7y = -6-8 -2y = -14 y = 7

6-1y+(5y-6y) = 6-y+(-1y) = 6

It is not possible to solve a single linear equation in two variables.

6 - y + 5y - 6y = 0 6 = y -5y + 6y 6 = -4y + 6y 6 = 2y 6/2 = y 3 = y

y/5 = y/6+9 Multiply all terms by 30 to eliminate the fractions 6y = 5y+ 270 Subtract 5y from both sides 6y-5y = 270 y = 270

Is this a system of equations? 2X + 5Y = 4 X + 5Y = 7 solve for X using bottom equation X = 5Y - 7 insert into top equation 2(5Y - 7) + 5Y = 4 distribute 10Y - 14 + 5Y = 4 solve for Y 15Y = 18 Y = 18/15 = 6/5 use bottom equation to find X X +5(6/5) = 7 X = 1 check with bottom equation 1 + 5(6/5) = 7 7 = 7 not true for top equation ( sorry, I forgot what happens then-resubmit question )

That would depend on the plus or minus value of 3y or maybe an equality is missing none of which have been given.